WEAVING HARMONY IN DIVERSITY: THE ROLE OF ISLAMIC RELIGIOUS EDUCATION, RELIGION, AND CULTURE IN A PLURALISTIC SOCIETY - Moh. Anas; Zamroni Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Harmony in a multicultural society is an important foundation for the creation of a peaceful, just, and sustainable social life. This article aims to examine the role of Islamic Religious Education (PAI), religion in general, and local culture in strengthening the values of tolerance and social integration in a pluralistic society. This study uses a descriptive qualitative approach with a literature study as the main method, collecting data from relevant religious, educational, and cultural literature. The results of the study indicate that PAI plays a strategic role in instilling the value of religious moderation, while other religions also voice universal humanitarian ethics. On the other hand, local culture is an effective medium in maintaining a shared identity and building bridges between groups. The implications of these findings emphasize the importance of collaboration between educational institutions, religious figures, and cultural actors in fostering inclusive and civilized social harmony